2022
DOI: 10.3390/ijerph19042380
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dental Fear and Anxiety, General Anxiety/Fear, Sensory Over-Responsivity, and Oral Health Behaviors and Outcomes: A Conceptual Model

Abstract: Dental fear and anxiety (DFA) is common across the lifespan and represents a barrier to proper oral health behaviors and outcomes. The aim of this study is to present a conceptual model of the relationships between DFA, general anxiety/fear, sensory over-responsivity (SOR), and/or oral health behaviors and outcomes. Two rounds of literature searches were performed using the PubMed database. Included articles examined DFA, general anxiety/fear, SOR, catastrophizing, and/or oral health behaviors and outcomes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 254 publications
(335 reference statements)
1
11
0
Order By: Relevance
“…Nevertheless, studies have shown that children with general anxiety and psychological disturbance tend to exhibit uncooperative dental behavior and anxiety problems. 19 , 20 , 21 , 22 , 23 Therefore, evidence of the effect of children's ST exposure on dental anxiety and behavior problems in dental clinics is needed. To our knowledge, only one article has discussed the relation between screen exposure and children's dental anxiety and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies have shown that children with general anxiety and psychological disturbance tend to exhibit uncooperative dental behavior and anxiety problems. 19 , 20 , 21 , 22 , 23 Therefore, evidence of the effect of children's ST exposure on dental anxiety and behavior problems in dental clinics is needed. To our knowledge, only one article has discussed the relation between screen exposure and children's dental anxiety and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The present IR clearly shows that to date, only five articles directly link PSD and clinical practices to pediatric dentistry [1,[7][8][9][10]. Nevertheless, all articles specifically discuss autism spectrum disorder (ASD), although some studies associate SPD with other diagnoses, such as attention deficit hyperactivity disorder (ADHD), Down syndrome and anxiety [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory processing patterns and alexithymia are also associated with pain catastrophizing [14,[19][20][21][22], which in turn is associated with dental anxiety [23,24]. Catastrophic thinking is known to contribute to the experience of pain by negative ruminating, and by magnifying and capturing the experience of pain [23].…”
Section: Introductionmentioning
confidence: 99%